THE EFFECT OF ORGANIC FERTILIZER OF ANIMAL SLAUGHTERHOUSE FERMENTED BY EM4 ON GROWTH AND YIELD OF Asystasia gangetica AT DIFFERENT LEVEL OF SOIL WATER CONTENTS - M. W., Bachtiar; Suryani, N. N.; Duarsa, M. A. P. (Jurnal Peternakan Tropika, 2022)
The purpose of this research was to study the interaction between slaughterhouse waste dose fermentated with EM4 and different soil water content and the effect each factor towards growth and crop production of Asystasia gangetica. This research has been done at glass house, Sesetan research station, Faculty of Animal Husbandry, Udayana University at Sesetan Road Markisa Alley. This research lasted 3 months, using a completely randomized design factorial system. The first factor was fertilizer dose : 0 ton/ha (D0), 10 ton/ha (D10), 20 ton/ha (D20) and 30 ton/ha (D30). The second factor was from soil water content : 50% field capacity, 75% field capacity and 100% field capacity. There are 12 combination of treatments and each treatment was three repeated, so there are 36 unit of expereiments. The variables that being observed was growth variable, yield variable and the growth characteristic variable. The research showed that there are no interaction between the dose of fertilizer from EM4 fermented waste animal slaughthouse and the soil water content of all variable. In the dose of fertilizer from EM4 waste animal slaughthouse showed that the highest result at dose 10 ton/ha (D10) and there was no significant difference from all variables except the dry weight of top ratio total of green with the dry weight of root. Soil water content showed that highest result at 100% field capacity and there was significant difference from all variables except the dry weight leaf with the dry weight stem and the dry weight of top ratio total of green with the dry weight of root. The conclusion from the result of this research was there is no treatment interaction between the dose of fertilizer from EM4 fermented waste animal slaughthouse treatment with the soil water content towards variable (growth variable, yield variable and the growth characteristics variable), fertilizer treatment of waste animal slaughter fermented by EM4 showed no effect on the growth and yield of Asystasia gangetica, but dose 10 ton/ha tend to show the highest result. Soil water content treatment 100% field capacity gave the best response in affecting growth and yield of Asystasia gangetica. Keywords : Asystasia gangetica, ground levels, fertilizer, growth